Features of Formation and Cryopreservation of Spheroids From Brain Cells of Newborn Rats - Vsevolodska, Svitlana; Sukach, Oleksandr; Ochenashko, Olga (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):288